Genetic analysis of TPM1 gene polymorphism (rs11071720) in patients with non-syndromic cleft lip/palate in the south indian population : a case control study = Análisis genético del polimorfismo del gen TPM1 (rs11071720) en pacientes con labio/paladar hendido no sindrómico en la población del sur de la India : estudio de casos - Murugesan, Dhakshinya
The aim of this study was to find out if there was an association between TPM1 gene polymorphism (rs11071720) and non-syndromic cleft lip and palate in humans. Twenty five patients with non-syndromic cleft lip and palate (NSCL/P) and twenty five healthy patients as controls were enrolled in the study. Whole blood drawn from the participants was used to obtain genomic DNA. Sequence specific primers were used to amplify the region spanning the polymorphic site of the TPM1 gene using polymerase chain reaction (PCR). The genotype of the subjects was identified employing the RFLP technique. The genotype and allele frequency distributions in the non-syndromic cleft lip and cleft palate patients and control groups were compared using Chi-square test. In the NSCL/P, the genotype in the order from highest to lowest frequency was TC (48%), followed by CC (32%) and TT (20%). Although the genotype frequency of the case and the control groups were found to be in agreement with Hardy Weinberg Equilibrium, the genotype frequencies TC, CC and TT of the polymorphism (rs11071720) among the two groups were not statistically significant which was evident from the p-value 0.8472. No significant association was found between TPM1 gene (rs11071720) polymorphism and NSCL/P.